MODEL INTEGRATIF COACHING-MENTORING DALAM SUPERVISI AKADEMIK: STUDI KASUS KEMANDIRIAN PEDAGOGIK GURU DI SMP AL AZHAR 48 SAMARINDA - Suharmi, Suharmi; Sumanti, Herlina; Eljohn, Grace; Warman, Warman; Yahya, Masrur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the implementation of an integrative coaching-mentoring model in academic supervision to enhance teachers' pedagogical autonomy, specifically at SMP Al Azhar 48 Samarinda. The background reveals gaps in teacher professional development programs in Southeast Asia, with 70% of teachers struggling to access quality initiatives. In Indonesia, 65% of private junior high school teachers find existing supervision programs disempowering. Supervision paradigms have shifted from administrative to collaborative approaches, yet implementation remains fragmented and lacks synergistic integration of coaching and mentoring. The study addresses three research gaps: the absence of an integrated supervision model, the administrative focus of current research in Indonesian private junior high schools, and the neglect of unique Islamic school values. Employing an intrinsic qualitative case study approach , this research will explore best practices and obstacles in collaborative, personalized, and value-driven academic supervision. Data was collected through semi-structured interviews, participant observation, and document analysis involving five teachers, two supervisors, and one school principal. Theoretically, this study contributes to forming a holistic supervision framework that combines instructional reflection (coaching) with sustained professional relationships (mentoring). Practically, the findings are expected to serve as an adaptive guide for similar private schools and inform policy considerations for relevant teacher supervision programs.